Proceedings of the second annual dengue endgame summit: A call to action. - Céline S C Hardy; Lauren E Bahr; Alan L Rothman; Kathryn B Anderson; Giovanna Barba-Spaeth; Daniela Weiskopf; Eng Eong Ooi; Ernesto T A Marques; Mattia Bonsignori; Alan D T Barrett; Beth D Kirkpatrick; Priscila M S Castanha; et al. (PLoS Neglected Tropical Diseases)
On August 7-9, 2024, the second annual dengue "endgame" summit was held in Syracuse, NY, hosted by the Global Health Institute at SUNY Upstate Medical University. The meeting brought together attendees from around the world, with talks spanning healthcare, government control programs, basic research, and medical countermeasure development efforts. The summit goal was to work toward a better understanding of what dengue control could look like and the steps required to reach such a goal. The objectives of the meeting were to discuss the current global state of dengue, what dengue "control" might look like, and to discuss actionable pathways for achieving dengue control. Topics covered throughout the meeting included DENV immunity and pathogenesis, challenges in countermeasure development, innovative vector control strategies, dengue diagnostics, addressing challenges in science communication, and vaccine hesitancy. Several fundamental knowledge gaps were repeatedly highlighted by the summit attendees and were cited as critical barriers to the development, deployment, and evaluation of effective dengue countermeasures. These gaps include (1) the lack of a broadly applicable immunologic biomarker/correlate of DENV immunity and (2) the lack of universally accepted/applicable metrics for quantifying dengue severity in the setting of countermeasure evaluations. In addition, the lack of clear and consistent international leadership in the global dengue control effort was cited as a barrier to widespread and synergistic research and countermeasure development/deployment activities. Despite these persistent roadblocks, summit attendees expressed optimism that holistic and multi-tiered approaches-incorporating optimal use of existing and nascent countermeasure technologies deployed in collaboration with local communities-could be effective in progressing toward dengue control.